Learn Python in One Hour Video Course - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2020)
This is a one hour introduction to Python with code samples you can execute at home at the same time. Code can be executed here: https://github.com/noahgift/functional_intro_to_python/blob/master/Public_Master_SafariOnline_Day1_Part1.ipynb Subscribe to YouTube channel: https://lnkd.in/gUpprB2 You can find more content by Noah Gift at https://noahgift.com. #pragmaticai #python #tutorial.